STRATEGY FOR IMPLEMENTING EXCELLENT SERVICE IN S LAUNDRY BUSINESSES IN THE NORTHERN HULU SUNGAI REGENCY - Nurul Hasanah; Maulida Putri (PPPM STIA Amuntai, 2025)
In this study discusses the application of excellent service strategies in the S Laundry business in Hulu Sungai Utara Regency. This research is based on the increasing competition in various businesses, especially Laundry services. Businesses engaged in services make the services provided to consumers as a measure of the success of the services provided in order to realize satisfAction to customer trust. The method used in this research is descriptive qualitative, which is an approach that aims to describe social phenomena that occur in depth. Data collection is done by in-depth interviews with customers, observation and documentation. Using purposive sampling technique in determining informant sample criteria. The results showed that employee friendliness and politeness were shown when serving customers, effective communication skills when serving customers, Attention shown to meeting customer needs, no mistakes in order processing, timely completion of orders and the Appearance of clean, neat and fragrant Laundry results. It can be concluded from the results of this study that the implementation of excellent service strategies at S Laundry is good, customers are satisfied with the services and results shown so that they benefit from customer trust and loyalty.